2020
DOI: 10.1155/2020/2651214
|View full text |Cite
|
Sign up to set email alerts
|

The Influence Mechanism and Optimization of the Sensor Network on the MS/AE Source Location

Abstract: The sensor network layout is a key factor affecting the accuracy and stability of the microseismic/acoustic source (MS/AE) location. Based on the arrival-time-difference principle, the hyperbolic/hyperboloidal governing equations for the source location are derived. The nonuniformity geometrical characteristics of hyperbolic/hyperboloidal field for the source location are obtained. The sensor network does not induce any location errors; it only affects the source location accuracy by amplifying the existing er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…With increasing micro-and macrocracks in the sample, the propagation of elastic waves in the sample becomes more complex, and the attenuation characteristics change significantly compared to those at the initial stage of loading. Furthermore, the fixed position of the AE sensor causes the signal strength and frequency received by a single AE probe to change significantly compared to the AE source [48,49]. At the later stage of loading, under the action of severe cracking, the AE sensor even falls off, or the coal attached to the sensor peels off from the main body of the sample.…”
Section: Difference Analysismentioning
confidence: 99%
“…With increasing micro-and macrocracks in the sample, the propagation of elastic waves in the sample becomes more complex, and the attenuation characteristics change significantly compared to those at the initial stage of loading. Furthermore, the fixed position of the AE sensor causes the signal strength and frequency received by a single AE probe to change significantly compared to the AE source [48,49]. At the later stage of loading, under the action of severe cracking, the AE sensor even falls off, or the coal attached to the sensor peels off from the main body of the sample.…”
Section: Difference Analysismentioning
confidence: 99%
“…Meanwhile, previous studies have shown that the arrangement of sensors has a significant impact on positioning accuracy [26]. Li et al [27] concluded that the sensor network does not introduce location errors but amplifies existing errors in input data during the source location process. They found that location accuracy decreases dramatically when the AE source is at the edge or outside the sensor arrangement.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some scholars have also studied the influence of MS network layout on positioning accuracy. Gong et al [20] have established a solution model suitable for largescale network combined planning for the MS monitoring system, aiming at the optimization problem of largescale network, effectively solving the layout and optimization problems of mine seismic network. Li et al [21] proposed sensor network optimization principles to improve positioning accuracy by studying sensor spatial layout.…”
Section: Introductionmentioning
confidence: 99%